Sintesis Kopoliester dari Îµ- Kaprolakton dan 2,2-dimetil-1,3-Propandiol: Prepolimer Alternatif untuk Sintesis Poliester Berat Molekul Tinggi - M. Hasan; S.I. Rahayu; I Made Arcana; Cynthia Linaya Radiman (Institut Teknologi Bandung, 2005)
Copolyesters from Îµ- caprolactone and 2,2-dimethyl-1,3-propanediol have been synthesized by using distannoxane as catalyst. The influence of monomer compositions on viscosity, melting point and structure of polyesters was studied. The results showed that the increase of Îµ- caprolactone content in copolymer increased the melting point and viscosity of polyester. This was supported by the decrease of hydroxyl number of polyester when the Îµ- caprolactone monomers in the copolymers increased.